2019
DOI: 10.1073/pnas.1906914116
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous relaxation and the high-temperature structure factor of XXZ spin chains

Abstract: We compute the spin structure factor of XXZ spin chains in the Heisenberg and gapped (Ising) regimes in the high-temperature limit for nonzero magnetization, within the framework of generalized hydrodynamics including diffusive corrections. The structure factor shows a hierarchy of timescales in the gapped phase, owing to s-spin magnon bound states ("strings") of various sizes. Although short strings move ballistically, long strings move primarily diffusively as a result of their collisions with short strings.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 78 publications
13
82
0
Order By: Relevance
“…Our results are consistent with a crossover time t c ∼ |m| 3 , in agreement with the prediction of Ref. [40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with a crossover time t c ∼ |m| 3 , in agreement with the prediction of Ref. [40].…”
Section: Discussionsupporting
confidence: 93%
“…In the following, we present an analysis of our numerical data that goes beyond the analysis shown in Ref. [40] and thereby confirm some of their analytic predictions. Short and intermediate times.…”
Section: Return Probabilitysupporting
confidence: 73%
“…Our model also predicts a crossover to a regime (σ/J) 1/2 < µ ≪ 1 in which the torsional mode becomes ballistic, with a propagation speed varying linearly in the initial magnetization, as v ball ∼ µ. This result was obtained from generalized hydrodynamics in the spin-1/2 Heisenberg chain 35 ; here we argue that the same phenomenon will arise in all quantum and classical integrable magnets with isotropic rotational symmetry. Indeed, this may explain the slow ballistic modes observed in very recent classical simulations 22 .…”
supporting
confidence: 69%
“…We emphasize that our derivation is "mesoscopic", in the sense that it fixes a particular coarse-graining length scale, l, and therefore excludes the recently discovered anomalous transport phenomena in the quantum spin-1/2 XXZ chain 35,36 , that emerge from linear fluctuating hydrodynamics in the limit of infinite coarse-graining length, l → ∞.…”
mentioning
confidence: 94%
“…Unexpectedly, a numerical study observed a third behavior at the isotropic (Heisenberg) point of this model [22,23]: spin dynamics at infinite temperature were characterized by superdiffusion with the same dynamical critical exponent z = 3/2, defined below, that appears in the classical, stochastic Kardar-Parisi-Zhang (KPZ) universality class [24]. This led to additional studies that explained how the diffusion constant must become infinite at the Heisenberg point [25] and showed agreement with the full KPZ scaling function [23,26]. Note that this emergence of superdiffusion and KPZ universality from quantum models is different from the su-perdiffusion with z = 1 that emerges in systems with momentum conservation [27,28] or the variable dynamical critical exponent at low temperatures in Luttinger liquids [29].…”
mentioning
confidence: 71%